2016
DOI: 10.1175/jas-d-15-0154.1
|View full text |Cite
|
Sign up to set email alerts
|

Extratropical Impacts on Atlantic Tropical Cyclone Activity

Abstract: With warm sea surface temperature (SST) anomalies in the tropical Atlantic and cold SST anomalies in the east Pacific, the unusually quiet hurricane season in 2013 was a surprise to the hurricane community. The authors' analyses suggest that the substantially suppressed Atlantic tropical cyclone (TC) activity in August 2013 can be attributed to frequent breaking of midlatitude Rossby waves, which led to the equatorward intrusion of cold and dry extratropical air. The resultant mid-to upper-tropospheric dryness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 84 publications
(65 reference statements)
3
32
2
Order By: Relevance
“…For example, the 2013 Atlantic hurricane season was characterized by warm sea surface temperature anomalies (SSTAs) in the Atlantic main development region (MDR) and cold SSTAs in the East Pacific, but turned out to be one of the quietest seasons since 1994 (Blake, ). Zhang et al (, ) suggested that the suppressed TC activity in 2013 can be attributed to active extratropical Rossby wave breaking (RWB). Despite a synoptic‐scale process, frequent RWB can induce significant large‐scale circulation anomalies on the seasonal time scale via enhanced tropical‐extratropical mixing and modulate TC activity.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the 2013 Atlantic hurricane season was characterized by warm sea surface temperature anomalies (SSTAs) in the Atlantic main development region (MDR) and cold SSTAs in the East Pacific, but turned out to be one of the quietest seasons since 1994 (Blake, ). Zhang et al (, ) suggested that the suppressed TC activity in 2013 can be attributed to active extratropical Rossby wave breaking (RWB). Despite a synoptic‐scale process, frequent RWB can induce significant large‐scale circulation anomalies on the seasonal time scale via enhanced tropical‐extratropical mixing and modulate TC activity.…”
Section: Introductionmentioning
confidence: 99%
“…The predictability, at least for short‐range predictions, appears largely limited by the atmospheric environment variables rather than the SST. Consistent with this finding, earlier studies suggest that the variability of extratropical atmosphere is not strongly constrained by the oceanic forcing (Kushnir et al, ; Lee et al, ; Sutton & Hodson, ) and is associated with lower prediction skills of TC activity (Bell et al, ; Fitzpatrick et al, ; Li et al, ; Wang et al, ; G. Zhang, et al, ). Overall, the skill of the FLOR‐FA prediction appears higher in regions where the potential predictability is higher.…”
Section: Summary and Discussionmentioning
confidence: 52%
“…In some cases, the lack of the extratropical influence allows the Fujiwhara effect to dictate storm motion. The difference might arise because they emphasized lateral boundary forcing from the 2013 season, which featured extratropical anomalies that were exceptionally strong and extended into the deep tropics (Bell et al, 2014;Zhang et al, 2016;Zhang et al, 2017). Finally, storm lysis in the Ncalm simulations occurs farther east and less frequently along the northern boundary than in the Default simulations.…”
Section: Responses To Modified Lateral Boundary Forcing: Climatologymentioning
confidence: 94%
“…Since the Default and the Ncalm experiments share the same SST forcing, the environmental changes can be causally attributed to the suppression of the weather perturbations at the northern boundary. The moistening tendency may occur because the suppression of the tropical-extratropical interaction reduces the mixing of the high-latitude dry air into the subtropics (e.g., Dunion, 2011;Galewsky et al, 2005;Zhang et al, 2016). The moistening tendency may occur because the suppression of the tropical-extratropical interaction reduces the mixing of the high-latitude dry air into the subtropics (e.g., Dunion, 2011;Galewsky et al, 2005;Zhang et al, 2016).…”
Section: Responses To Modified Lateral Boundary Forcing: Climatologymentioning
confidence: 99%
See 1 more Smart Citation